Chemotherapy-free innovations in locally advanced head and neck cancer: a comprehensive review - Abu Taha, Shatha; Abu Hejleh, Taher; ElHaddad, Mostafa; Al-Ibraheem, Akram; Abbasi, Ahmed; Sumaida, Abdulrahman; Bushehri, Ahmad; Mostafa, Ahmad; Youssef, Bassem; Alotain, Ibrahim; Abu-Gheida, Ibrahim; Aldehaim, Mohammed; et al. (Frontiers in Oncology, 2025)
The treatment of locally advanced head and neck squamous cell carcinoma (LA-HNSCC) has traditionally relied on a multimodal approach, combining surgery, radiation therapy (RT), and chemotherapy. While chemotherapy plays a critical role in improving cure rates and functional outcomes, its substantial toxicity remains a major concern, particularly in older patients. These challenges are especially relevant for those who are unfit for chemotherapy or decline conventional concurrent chemoradiotherapy (CCRT), highlighting the need for alternative therapeutic options. Many patients are at high risk for severe side effects, often preventing them from completing the full chemotherapy regimen. This review explores alternative strategies to definitive CCRT of carcinomas of the larynx, hypopharynx and oropharynx, aiming to optimize treatment outcomes while minimizing toxicity. We discuss altered fractionation strategies as a promising alternative to conventional RT, offering a balance between treatment efficacy and quality of life. Additionally, we examine emerging approaches, including the combining of targeted therapies, immunotherapy, hyperthermia, photodynamic therapy and nanoparticle-based treatments with RT, which provide alternative or complementary options to traditional therapies in the management of LA-HNSCC.